The last green valley : a novel - Sullivan, Mark T. (Lake Union Publishing, 2021)
In late March 1944, as Stalin's forces push into Ukraine, young Emil and Adeline Martel decide they must run in retreat from their land with murderous Nazi officers they despise to escape the Soviets and go in search of freedom.